Pembuatan Scaffold Trikalsium Fosfat Berpori Menggunakan Metode Protein Foaming-Consolidation Dengan Variasi Waktu Dan Temperatur Pengeringan - Gede Indra Ludy Wirata; Ahmad Fadli; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tricalcium phosphate (TCP) is a ceramics material which is widely used for bone subtitude. Protein foaming-consolidation method is a technique for production of porous tricalciumphosphate (TCP) using egg yolk as pore creating agent. The purpose of this research was to investigate the effect of time and drying temperature effect on physical, chemical and mechanical properties of porous TCP and characterizing porous TCP as bones implant. This research start by mixing TCP powder, sago powder, Darvan 821A and egg yolk. The slurries were mechanical stirred at 150 rpm for 3 hours. Then, the slurries were casted in a cylindrical stainless stell moldand heated at 160oC, 180°C and 200oC for 5, 10, 15, 20, 30, 40, 50 and 60 minutes. Subsequently, dried samples were demolded and burned at 600°C for 1 hour.,For the final steps,samples were sintered at 1150oC for 1 hour. The results of porous TCP from this research was 45.90-61.70% for porosity, the density was 1.20-1.72 g/cm3 and the compressive strength was 8.04-8.64 Mpa.Keyword : tricalcium phosphate, egg yolk, porosity, density, compressive strength